2001
DOI: 10.1016/s0022-2275(20)31619-9
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus-mediated expression and purification of human serum paraoxonase 1A

Abstract: Human paraoxonase 1 (hPON1) is a lipid-associated enzyme transported on HDL. There is considerable interest in hPON1 because of its putative antioxidative/ antiatherogenic properties. We have created a recombinant baculovirus (BV) to generate hPON1A in large quantities for structure-function studies and here describe the method for production and isolation of the enzyme. A high level of recombinant hPON1 type A (rPON1A) was produced by Hi-5 insect cells (40 mg/l); a fraction ( ϳ 10 mg/l) was secreted into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…PON1 retains the signal peptide that is usually removed after protein translocation and is likely related to the protein property of binding to HDLs [40]. PON1 is also highly glycosylated, which makes it difficult to produce recombinantly.…”
Section: Structural Insight Into the Active Site Of Pon1mentioning
confidence: 99%
See 1 more Smart Citation
“…PON1 retains the signal peptide that is usually removed after protein translocation and is likely related to the protein property of binding to HDLs [40]. PON1 is also highly glycosylated, which makes it difficult to produce recombinantly.…”
Section: Structural Insight Into the Active Site Of Pon1mentioning
confidence: 99%
“…PON1 is also highly glycosylated, which makes it difficult to produce recombinantly. The first attempts to produce recombinant PON1 in E. coli resulted in aggregated proteins [40,41]. The soluble form of rePON1 produced in E. coli was obtained by DNA shuffling of human, mouse, rat and rabbit PON1 genes.…”
Section: Structural Insight Into the Active Site Of Pon1mentioning
confidence: 99%
“…16,35 Furthermore, the K app M values for both recombinant and wild-type PON1 forms are well in agreement with previously reported K M values (0.8-1.4 mM) for paraoxon. 6,32,33,36 These parameters were obtained by conventional UV-Vis spectrophotometry, following the formation of p-nitrophenol over time by monitoring the increase in absorbance at 412 nm. 4,6,32,33,36 Although such techniques allow for a high throughput sample analysis, they require specialized equipment, such as microplate readers, that do not offer the same miniaturization degree as electrochemical methods.…”
Section: Paraoxonase Activitymentioning
confidence: 99%
“…6,32,33,36 These parameters were obtained by conventional UV-Vis spectrophotometry, following the formation of p-nitrophenol over time by monitoring the increase in absorbance at 412 nm. 4,6,32,33,36 Although such techniques allow for a high throughput sample analysis, they require specialized equipment, such as microplate readers, that do not offer the same miniaturization degree as electrochemical methods. Frequently, UV-Vis assays are performed at basic pH to improve the sensitivity, as the p-nitrophenol molar extinction coefficient is particularly high above pH 8.…”
Section: Paraoxonase Activitymentioning
confidence: 99%
“…Characterization of the substrate specificities of the purified recombinant PONs is described below. Brushia et al (2001) had earlier reported the expression and purification of PON1 Q192 from a baculovirus expression system.…”
mentioning
confidence: 99%